Geometria plana: um estudo sobre o quadrado com alunos do 7º ano do Ensino Fundamental sob a ótica da Teoria de Van Hiele - Franklin Fernando Ferreira Pachêco; Gisele Ferreira Pachêco (Revista Principia, 2017)
The objective of this work is to analyze the level of geometric knowledge of students of the 7th year of Elementary School, through the study of the square, mediated by Van Hiele Theory, which aims to verify the level of geometric knowledge through Of five levels of understanding in a hierarchical way. In addition, it serves as a contribution for the teacher to organize his classes and to identify the existing gaps about the geometric knowledge that the students possess, through a content, especially the one of the flat geometry. We approach a qualitative methodology with a diagnostic character. Participated in this work 26 students of the 7th grade of Elementary School of a public school, located in the municipality of São Vicente Férrer-PE. In this paper, we use two questions from a test. The first question presented a set of polygonal and non-polygonal figures, aiming at the students to identify the squares, from their physical form. The second question had as objective to verify if the students quoted the properties of the squares, exposing a greater knowledge of this geometric figure. According to the protocols presented by the students, the first question - which referred to the identification of the square from its physical form - presented a high success rate. The second question, which related to the properties of the square, presented a low success rate. Before our analysis, we can verify that, in the identification of the squares by means of their physical form, there is no evidence of difficulties by the students, but there is a certain fragility to cite their properties. In general, therefore, we analyze the protocols of the students, according to the levels of understanding of Van Hiele Theory, noting that these correspond to the level of analysis, because they are progressing in the perception of geometric knowledge, especially in the figure of the square